Effects of external diaphragm pacing combined with repetitive peripheral magnetic stimulation of the phrenic nerve on respiratory function in stroke patients - Zhang, Qin; Wang, Chengshuo; Cai, Hongfei; Jin, Shasha; Wang, Qian; Fu, Yanxin; Xiang, Aomeng; Qi, Jingman; Wu, Liang; Liu, Bin (Frontiers in Medicine, 2025)
ObjectivesTo investigate the effects of external diaphragmatic pacing (EDP) and repetitive peripheral magnetic stimulation (rPMS) of the phrenic nerve on respiratory function in stroke patients.MethodsFifty-four stroke patients were randomly assigned to three groups: an EDP group (n = 18), an rPMS group (n = 18), and a combined treatment group (n = 18). All groups received routine breathing training. Additionally, the EDP group underwent EDP, the rPMS group received repeated peripheral magnetic stimulation of the phrenic nerve, and the combined treatment group received a combination of both interventions. The treatment regimen lasted for 4 weeks. Pulmonary function parameters, including forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), FEV1/FVC%, peak expiratory flow (PEF), maximal inspiratory pressure (MIP), and maximal expiratory pressure (MEP), were assessed using a pulmonary function tester. Diaphragmatic thickness (DT) and diaphragmatic excursion (DE) were evaluated via ultrasound imaging, whereas compound muscle action potential (CMAP) amplitude and phrenic nerve conduction time (PNCT) were measured using transcranial magnetic stimulation technology.ResultsFollowing 4 weeks of treatment, significant improvements were observed in FVC, FEV1, PEF, MIP, and MEP across all three groups (all p < 0.05). Moreover, the combined treatment group demonstrated significantly greater improvements in FVC, FEV1, and MIP compared with either the EDP or rPMS group (p < 0.05). DT and DE were also significantly increased in all groups (p < 0.05), with more pronounced improvements in the combined treatment group than in the other groups (p < 0.05). In all three groups, CMAP amplitude increased significantly, whereas PNCT decreased significantly (p < 0.05). Furthermore, the reduction in PNCT was more obvious in the combined treatment group than in either the EDP or rPMS group (p < 0.05).ConclusionCompared with monotherapy using either EDP or rPMS, combined treatment demonstrates significantly greater efficacy in promoting respiratory function rehabilitation in stroke patients. Additionally, it shows potential advantages in improving phrenic nerve motor conduction.